Peningkatan Motivasi dan Minat Belajar Siswa pada Mata Pelajaran Al-Quran Hadis melalui Game New Family 100 Berbasis Kahoot di Kelas 7A MTS No 32 Lamasi - Masykur, Masykur Zaini (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
This study aims to enhance students’ motivation and interest in learning Al-Qur'an Hadith through the use of the Kahoot-based "New Family 100" game in class 7A of MTs No. 32 Lamasi. The research addresses the question: Can the implementation of this game improve students' motivation and interest in learning Al-Qur'an Hadith? The study uses a Classroom Action Research (CAR) approach, conducted in two cycles. Each cycle involved group-based, interactive learning that actively engaged all students through the game. Findings show that students' motivation and interest improved significantly after the implementation. Motivation increased from 59.99% in Cycle I (moderate) to 78.33% in Cycle II (high), while interest rose from 61.90% (moderate) to 86.82% (high). Student observation results improved from 74.07% (fairly good) to 94.44% (very good), and teacher observations increased from 75.29% to 96.29% across the two cycles. These results indicate that the integration of interactive digital games like Kahoot in religious studies can effectively enhance student engagement and enthusiasm.